Pelatihan Bahasa Inggris bagi Anak Sekolah Dasar Kelas Atas - Heriyanto, Dwi; Widiyono, Ibnu Prasetyo; Hapsari, Novita; Maslikhah, Nur Laeli (Universitas Ma'arif Nahdlatul Ulama Kebumen, 2025)
Basic English Training is a learning program designed to help participants understand and master the basics of English. The purpose of this training is to improve communication skills and help participants understand and use English to speak, listen, read, and write in everyday and formal situations. The results of basic English training usually reflect an increase in participants' ability to master the basics of English basic English training usually reflects an increase in participants' ability to master the basics of English. Some of the results that can be expected after completing basic English training include improving basic vocabulary understanding, participants are able to recognize and use basic words that are often used in everyday life, such as nouns, verbs, and common expressions. Ability to make simple sentences Participants can compose simple sentences with correct grammar, for example introducing themselves, providing basic information, or asking simple questions. Improving basic speaking skills so that participants can communicate in English with simple sentences, for example introducing themselves, talking about hobbies, or asking for information. The objects in this training are upper-class students of SD Negeri 1 Bumirejo, Kebumen District. This program is one of the strategies to improve English literacy in elementary schools. Furthermore, this program can be expanded to other schools by involving local communities and society to provide wider access to students to develop their English language skills